VD_FINDINFO HC / 2012 / 687 vom 13. September 2012 - VD Tribunal cantonal (2012)
DISPOSITIF, RECOURS DIRECT, FRAIS JUDICIAIRES, DÉPENS, RÉPARTITION DES FRAIS | 91 CPC, 92 al. 2 CPC, 319 let. a CPC (CH), 404 al. 1 CPC (CH), 405 al. 1 CPC (CH)